PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBER HEAD TOGETHER) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 88 PEKANBARU - Susilawati '; Hendri Marhadi; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research was mathematic learning outcomes in fourth grade students SDN 004 Pekanbaru still low with average value 60,1 with minimum completeness criteria (KKM 70).The purpose 0f this research was to improve mathematic learning outcomes 0f the fourth grade (IV) students SDN 88 Pekanbaru with the implementation of number head together (NHT) models. This research was classroom action research with two circles. The subject were students of class IV SDN 88 Pekanbaru on 2016/2017 academic years with amounted to 33 students consisting of 12 men and 21 women. Base on analysis result observation paper of teacher and students activity sheet seen rising each meeting, teacher activity at first meeting of first circle was 79,1 % good category and at the second meeting was 87,5 % with very good category. At the second circle, teachers activity at the first meeting was 91,7 % and the second meeting was 95,8 % with very good category. Student activities at first meeting of first circle was 70,8 % good category and at the second meeting was 83,3 % with very good category. At the second circle, student activity on the first meeting was 87,5 % and at the second meeting was 91,7 % with very good category. Mathematic learning outcomes before implementation cooperatives number head together type learning model average 60,1, after implementation cooperatives number head together type learning model at UH 1 was 75,2 and at UH II was 84,3 that improve about 40,3 %. Implementation of cooperatives number head together type learning model can improve learning outcomes of the fourth grade students SDN 88 Pekanbaru. Key Words: Cooperatives Number Head Together Type Learning Model, Mathematic Studies Achievement